Gangguan ginjal akut pada keadaan kritis - Putri Amelia; Munar Lubis; Yunnie Trisnawati (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Acute kidney injury is characterized by a reversibe increase in the blood concentration of creatinine an nitrogenous waste products and by the inability of the kidney to regulate fluid and electrolyte homeostasis approprietly. Acute kidney injury is increasingly recognized as a cause of increased morbidity in critically ill children and adults, and affects patient survival. Acute kidney injury is known to be an independent risk factor for mortality, and research pursues optimization of diagnosis, management, and outcome.Key words : acute kidney injury; critical ilness